Retrospective Analysis of the Accuracy of High-Frequency Ultrasound for Pancreaticobiliary Maljunction in Pediatrics at a Single Center - Xu, Qiuchen; Liu, Min; Wu, Qiumei; Ling, Wen; Guo, Shan (Frontiers in Pediatrics, 2022)
Objective To determine the clinical value of high-frequency ultrasonography (US) in the evaluation and diagnosis of pancreaticobiliary maljunction (PBM) among children. Methods The clinical subjects consisted of 31 pediatric patients who were diagnosed with PBM from January 2015 to May 2021 in Fujian Provincial Maternity and Children's Hospital. The primary outcomes included diagnosis accuracy, imaging characteristics of each type of PBM based on JSPBM, time length of operation, and cost of service. Secondary outcomes were the serum amylase and bilirubin levels. Results The diagnostic accuracy of US was 90.3% and comparable to the other imaging methods—MRCP (82.6%), IOC (79.2%), and ERCP (100%), respectively. The time length of operation and direct cost were significantly lower than other imaging pathways. Stenotic type (A) is associated with a high internal diameter of CBD, and dilated channel type (C) presents increased internal diameter and length of CC as well as internal diameter of PD. There were higher levels of the serum bilirubin seen in type A and of serum amylase in type C compared with others. Conclusion High-frequency US is a safe, cost-effective, and non-invasive imaging tool for the diagnosis and evaluation of PBM in pediatrics.